Use of adaptable empirical equations for potential evapotranspiration estimation and soil moisture balance approaches for estimating actual evapotranspiration - Abdurahman, M.A.; Coldewey, W. G.; Mohn, R.; Werner, J.; Awulachew, Seleshi Bekele; Kruse, B.; Klemm, O. (2008)
Evapotranspiration is an important component of the hydrologic cycle. In this research, an attempt has been made to estimate the potential and actual evapotranspiration combining different approaches that can be easily adapted in many of the irrigation projects found in the Tigray region of Ethiopia. There is no established weather station in these project areas. Therefore, it was not possible to use more complicated equations like the Penman family to estimate the potential evapotranspiration that can be used during planning and operation of irrigation projects. Thus, as an alternative in this research, an empirical equation that uses less data input has been adapted and then calibrated with the estimated values from the Modified Penman equation. To undertake this study three reference weather stations, having better data set of recent years, were selected. The potential evapotranspiration is estimated by the Hargreaves and Samani, as well as the Modified Penman equations. The potential evapotranspiration estimated by the two methods for the three reference stations were fitted into a straight line resulting equation with an acceptable correlation of (R2) = 0.8. Therefore, in the absence of other actual measured data for the irrigation projects, the potential evapotranspiration can be estimated by the Hargreaves and Samani method and corrected with the equation developed from the calibration procedure mentioned above. Furthermore actual evapotranspiration is also calculated for the watersheds of two irrigation projects (Laelay Wukro and GumSelassa). To undertake this exercise the landuse and soil maps of each watershed were prepared at a 1:50,000 scale and aggregated to get a combined landuse and soil for each watershed. Depending on the soil type, the available soil moisture per depth for each landuse was fixed, considering an acceptable rooting depth for the corresponding landuses. Then spreadsheets were developed to determine the monthly water balance taking into account that soil moisture storage withdrawal linearly decreases with decreasing soil moisture, i.e. as the soil becomes dry it becomes more difficult to remove water from the soil and hence less water is available for actual evapotranspiration. Accordingly, the actual evapotranspiration is found to be 627 and 442 mm year-1 for Laelay Wukro and GumSelassa irrigation projects respectively, which is about 44% and 32% of the potential evapotranspiration.